1991
DOI: 10.1037/0278-7393.17.5.963
|View full text |Cite
|
Sign up to set email alerts
|

Conditions and consequences of maintenance rehearsal.

Abstract: The present experiments investigated the idea that the anticipated delay to initial recall governs whether a subject will rely on elaborative or maintenance rehearsal. In agreement with earlier research, the results suggested that maintenance rehearsal is used only when words can be rehearsed up to the moment of recall. A novel finding concerned the accessibility of the items processed in that way. When subjects were explicitly asked to recall those items first in final free recall, they were as likely to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Many studies have observed that so-called elaborative rehearsal can be beneficial to performance, with the suggestion that this is more evident when participants anticipate having to recall that information after a delay (e.g., Craik & Watkins, 1973;Wixted, 1991;Wixted & McDowell, 1989). Many studies have observed that so-called elaborative rehearsal can be beneficial to performance, with the suggestion that this is more evident when participants anticipate having to recall that information after a delay (e.g., Craik & Watkins, 1973;Wixted, 1991;Wixted & McDowell, 1989).…”
Section: Extension To Other Domains and Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have observed that so-called elaborative rehearsal can be beneficial to performance, with the suggestion that this is more evident when participants anticipate having to recall that information after a delay (e.g., Craik & Watkins, 1973;Wixted, 1991;Wixted & McDowell, 1989). Many studies have observed that so-called elaborative rehearsal can be beneficial to performance, with the suggestion that this is more evident when participants anticipate having to recall that information after a delay (e.g., Craik & Watkins, 1973;Wixted, 1991;Wixted & McDowell, 1989).…”
Section: Extension To Other Domains and Paradigmsmentioning
confidence: 99%
“…Many studies have observed that so-called elaborative rehearsal can be beneficial to performance, with the suggestion that this is more evident when participants anticipate having to recall that information after a delay (e.g., Craik & Watkins, 1973;Wixted, 1991;Wixted & McDowell, 1989). More generally, the finding that participants show little long-term benefit from rehearsal when retdeval is expected immediately (Craik & Watkins, 1973;Wixted, 1991) could be explained by participants selectively failing to learn about the group context for that information (thus reducing the retroactive and proactive interference at the group level when attempting to retrieve other information from the same list). In addition, the reduced output leaming assumed for the last group in a list (the parameter TI°"J) could explain the poor long-term recall of recency items despite the benefits of rehearsal to their initial recall (Wixted & McDowell, 1989).…”
Section: Extension To Other Domains and Paradigmsmentioning
confidence: 99%
“…Heuer and Reisberg (1990) compared the effects of instructions to memorize slides with the effects of an emotional context produced by an accompanying narration. Whereas instructions to memorize enhanced memory, they enhanced memory for central plot 1 The term rumination is used here in preference to the more commonly used term, rehearsal, because studies have shown that increased rehearsal time per se does not generally enhance subsequent recall (Craik & Watkins, 1973;Wixted, 1991). On the other hand, retrieving a memory that is not already in working memory has a substantial effect (e.g., Allen, Mahler, & Estes, 1969;Carrier & Pashler, 1992;Izawa, 1970), as does elaboration (Craik & Watkins, 1973).…”
Section: Explaining Emotionality Effectsmentioning
confidence: 99%
“…Ces données chronopsychologiques sont à rapprocher des études expérimentales portant sur la mémorisation de listes de mots. Ainsi, de nombreuses recherches (Craik & Lockhard, 1972 ;Greene, 1987 ;Rundus, 1977 ;Wixted, 1991) tendent à montrer que les sujets débutent l'apprentissage d'une liste de mots en employant des processus de répétition élaborée, ceux-ci faisant place, en cours de liste, à des processus de répétition subvocale plus automatique pour les derniers items présentés.…”
Section: 1 Fluctuations Circadiennes De Mémorisation Chez L'adulteunclassified